Nimesulide derivatives reduced cell proliferation against breast and ovarian cancer: synthesis, characterization, biological assessment, and crystal structure: DOI: 10.48129/kjs.16735 - Jarragh Alhadad, Laila Abdulmohsen (Kuwait Journal of Science, 2022)
New nimesulide derivatives (A1-A6) synthesized and investigated by IR, 1H NMR, 13C NMR spectra, melting point, and DSC analysis. Ligand formula were assigned based on the elemental analysis, mass spectra. Agent A3’s single crystal was grown and solved as monoclinic with C 1 c 1 space group. Heat shock protein 27 (HSP27) and tubulin proteins are important cellular proteins for normal cell division and growth, which are elevated in cancer cells. Breast cancer (SKBR3) and ovarian cancer (SKOV3) cell lines were used as a model for the biological assessment. The data revealed that nimesulide analogues showed high cytotoxicity when treated with SKBR3 cell line ranges from 0.22 µM to 12.0 µM, while SKOV3 cell line ranges from 0.1 µM to 16.0 µM. In depth, structure activity relationship applied on nimesulide skeleton, highlight the importance of a bulk moiety on position two that induce apoptosis in both cell lines.